2017
DOI: 10.1186/s13104-017-2763-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of psychoactive substances use among Woldia University students in Northeastern Ethiopia

Abstract: BackgroundPsychoactive substance use has become a major public health problem among students in Ethiopian universities. Hence, this study aimed to investigate the magnitude and determinants of psychoactive substances use (khat chewing, alcohol drinking and cigarette smoking) among undergraduate students of Woldia University, Ethiopia.MethodsInstitution based quantitative cross-sectional study was employed on Woldia University students in April 2015. 730 students were included in the study. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 14 publications
(39 reference statements)
6
61
4
Order By: Relevance
“…From the pooled effect size of four studies, those students who had history of khat chewing were 6.55 times more likely to smoke cigarettes as compared to nonkhat chewers (6.55 (95% CI: 2.81-15.26; I 2 � 82.5)) [22,23,31,32]. e finding of this study also showed that those students who had history of alcohol use were 11.2 times more likely to smoke cigarettes (11.16 (95% CI: 7.46-16.71; I 2 � 0.0%)) [22,23,28,32] ( Figure 6).…”
Section: Factors Associated With Cigarette Smoking Among Ethi-supporting
confidence: 50%
See 1 more Smart Citation
“…From the pooled effect size of four studies, those students who had history of khat chewing were 6.55 times more likely to smoke cigarettes as compared to nonkhat chewers (6.55 (95% CI: 2.81-15.26; I 2 � 82.5)) [22,23,31,32]. e finding of this study also showed that those students who had history of alcohol use were 11.2 times more likely to smoke cigarettes (11.16 (95% CI: 7.46-16.71; I 2 � 0.0%)) [22,23,28,32] ( Figure 6).…”
Section: Factors Associated With Cigarette Smoking Among Ethi-supporting
confidence: 50%
“…In this study, a total of 7,861 study participants were included from 13 studies. ese studies were carried out from January 2011 to December 2018 from 10 different universities in seven regions of the country: Addis Ababa � 1, Amhara � 3, Dire Dawa � 1, Oromia � 1, Somali � 2, SNNPR � 3, and Tigray � 1 [22][23][24][25][26][27][28][29][30][31][32][33][34]. All of the studies included were cross-sectional with a sample size ranging from 271 to 1022 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Who had ever drunk alcohol and ever smoked cigarette were more likely to practise chewing as compared to no alcohol and cigarette users. This finding is supported by r studies conducted, ever drunk alcohol [52,54], and smoking cigarette [43,48,50,52,54]. These studies reported that history of alcohol consumptions and cigarette smoking was positively associated with chewing.…”
Section: Discussionmentioning
confidence: 65%
“…This significant difference between male and female may be justified as; females are less exposed to chewing practice than males. Moreover, we found that being Muslim by religion had a significant role to be user than others [2,36,41,43,51,52].…”
Section: Discussionmentioning
confidence: 81%
“…About 80% of tobacco users are from low or middle income countries [9][10][11][12][13]. Despite a slight decline among the general population in the past decade globally [2] and nationally [11], recent evidence shows a higher prevalence of substance use among students attending higher educational institutions in Ethiopia and other low or middle income countries [12][13][14][15]. Following completion of pre-university education, students from areas of the country where substance use is common enroll at Ethiopian universities, including Mekelle University.…”
Section: Introductionmentioning
confidence: 99%